Mathematics
kikmanz
9

What is the solution of the system of equations below? 2x + 3y = 7 x + y = 3 (1) (1,2) (2) (2,1) (3) (4,-1) (4) (4,1)

+0
(2) Answers
Gracie216

[latex]\begin{cases}2x + 3y = 7 \\ x + y = 3 \ \ / *(-2) \end{cases}\\ \\\begin{cases}2x + 3y = 7 \\ -2x - 2y = -6\end{cases}\\+ \ ------- \\y=1\\ \\2x + 3\cdot1 = 7[/latex] [latex]2x+3=7 \ \ |-3\\ \\ 2x+3-3=7-3\\ \\2x=4 \ \ /:2 \\ \\x=2 \\ \\ \begin{cases} x=2 \\ y=1 \end{cases}[/latex]

rishimisra15

2x + 3y = 7 x + y = 3 x = 3 - y substituting for x, 2(3 - y)  + 3y = 7 = 6 - 2y + 3y = 7 6 + y = 7 thus, y = 1 x = 3 - y = 3 - 1 = 2. Thus, x = 2 , y = 1 Thus, (2) is correct.

Add answer